The Struggle between the Principle of Benefits and the Principle of Justice in Capital Gains Taxation - Krisman Gulo, Karunia; Isnaini, Isnaini (JURNAL MERCATORIA, 2025)
This article concerns Indonesian taxation of capital gains and the conflict between the benefits principle and the justice principle. It has been revealed that the Indonesian tax system is a mix of policies. However, the benefit principle is the leader in taxing capital gains in the capital market (for instance, there is a final rate of only 0.1% imposed on shares of the Stock Exchange). The policy is done to give a push to investment and make the tax administration more efficient. On the other hand, the justice principle is more potent in off-exchange transactions, where progressive rates are applied. The problem is focused on the point of view of efficiency; the pro-benefit policy is a significant source of distortions in the allocation of resources; from the point of view of distribution, the policy is regarded as unfair because it encumbers the labor income more than capital income, thus possibly causing economic inequalities and infringing on the principles of horizontal and vertical justice. In order to approach this problem, a theoretical reference is used. The data is collected through doctrinal legal research and observation. Those data were then analyzed qualitatively. This study concluded that to achieve a better balance than the current one, the researchers have suggested several measures, including adjusting the final share rate, treating short-term and long-term capital gains differently, establishing an inflation adjustment mechanism, and strengthening tax data integration.